Local democracy in Ukrainian cities: civic participation and responsiveness of local authorities. Issue 2 (3rd March 2016) - Aasland, Aadne; Lyska, Oleksii
Abstract : This article examines local democracy in Ukrainian cities from the perspective of the local population, with a focus on citizen participation and city authorities' responsiveness to the concerns of local inhabitants. It draws on a survey of 2000 urban residents in 20 Ukrainian cities with a diversity of population size, administrative status, and geographic location. Correspondence analysis is used to show how different groups of the population are distributed along the two dimensions of responsiveness of local authorities and citizen participation. A typology of four ideal-types of city residents is elaborated: "alienated, " "protesters, " "compliant, " and "interactive." The data reveal remarkably large differences among cities: from four to six of the cities are associated with each of the four typology categories based on the clustering patterns along the two dimensions. The main policy implication of the study is that general measures for local government reform should be combined with targeted measures directed at the various types of challenges experienced in different Ukrainian cities.